Organic Copper Speciation by Anodic Stripping Voltammetry in Estuarine Waters With High Dissolved Organic Matter - Pađan, Jasmin; Marcinek, Saša; Cindrić, Ana-Marija; Santinelli, Chiara; Retelletti Brogi, Simona; Radakovitch, Olivier; Garnier, Cédric; Omanović, Dario (Frontiers in Chemistry, 2021)
The determination of copper (Cu) speciation and its bioavailability in natural waters is an important issue due to its specific role as an essential micronutrient, but also a toxic element at elevated concentrations. Here, we report an improved anodic stripping voltammetry (ASV) method for organic Cu speciation, intended to eliminate the important problem of surface-active substances (SAS) interference on the voltammetric signal, hindering measurements in samples with high organic matter concentration. The method relies on the addition of non-ionic surfactant Triton-X-100 (T-X-100) at a concentration of 1 mg L-1. T-X-100 competitively inhibits the adsorption of SAS on the Hg electrode, consequently (1) diminishing SAS influence during the deposition step and (2) strongly improving the shape of the stripping Cu peak by eliminating the high background current due to the adsorbed SAS, making the extraction of Cu peak intensities much more convenient. Performed tests revealed that the addition of T-X-100, in the concentration used here, does not have any influence on the determination of Cu complexation parameters, and thus is considered "interference free". The method was tested using fulvic acid as a model of natural organic matter and applied for determination of Cu speciation in samples collected in the Arno River estuary (Italy) (in spring and summer), characterized by a high dissolved organic carbon (DOC) concentration (up to 5.2 mgC L-1) and anthropogenic Cu input during the tourist season (up to 48 nM of total dissolved Cu). In all the samples two classes of ligands (denoted as L1 and L2) were determined in concentrations ranging from 3.5±2.9 to 63±4 nM eq Cu for L1 and 17±4 to 104±7 nM eq Cu for L2, with stability constants logKCu,1 = 9.6±0.2 - 10.8±0.6 and logKCu,2 = 8.2±0.3 - 9.0±0.3. Different linear relationships between DOC and total ligand concentrations between the two seasons suggest a higher abundance of organic ligands in the DOM pool in spring, which is linked to a higher input of terrestrial humic substances into the estuary. This implies that terrestrial humic substances represent a significant pool of Cu binding ligands in the Arno River estuary.